Metal- and additive-free C–H oxygenation of alkylarenes by visible-light photoredox catalysis. Issue 9 (21st April 2021) - Uygur, Mustafa; Kuhlmann, Jan H.; Pérez-Aguilar, María Carmen; Piekarski, Dariusz G.; García Mancheño, Olga
Abstract : A metal- and additive-free methodology for the highly selective, photocatalyzed C–H oxygenation of alkylarenes under air to the corresponding carbonyls is presented. Abstract : A metal- and additive-free methodology for the highly selective, photocatalyzed C–H oxygenation of alkylarenes under air to the corresponding carbonyls is presented. The process is catalyzed by an imide-acridinium that forms an extremely strong photooxidant upon visible light irradiation, which is able to activate inert alkylarenes such as toluene. Hence, this is an easy to perform, sustainable and environmentally friendly oxidation that provides valuable carbonyls from abundant, readily available compounds.